The Impact of Discovery Learning with a Scientific Approach in Mathematics Learning. Issue 1 (May 2021) - Alimuddin,; Mulbar, U; Rahmadani,
Abstract: This study aimed to determine the impact of discovery learning with a scientific approach in mathematics learning on junior high school students in Makassar city. The research samples were students of class VIII MTs Negeri Model Makassar. Data collection methods in this research were test and interview. The test method was used to obtain learning outcome data. While interviews were conducted to obtain data about the impact of discovery learning with the scientific approach in student mathematics learning outcomes. The analysis techniques used were descriptive statistics and inferential statistics. The results of descriptive and inferential analysis showed that the average score of student mathematics learning outcomes in experimental class was 91.33 with classical completeness around 97%. It showed student learning outcomes increased after the discovery learning with the scientific approach was applied. Thus, discovery learning with the scientific approach was better than conventional learning.